PENGARUH MEKANISME PENGAWASAN STAKEHOLDER TERHADAP TINDAKAN AGRESIVITAS PAJAK - Noor Faizah Ariyani; Puji Harto (Diponegoro Journal of Accounting, 2014)
This study aims to examine the influence of stakeholder’s oversight mechanism consisting of: board of commissioner meeting frequency, audit committee independence, audit committee competency, audit committee meeting frequency, auditor specialization in industry, audit tenure, leverage and litigation concentration on  tax aggressiveness which measured by cash effective tax rate (CETR).The population of this research are listed manufactured companies in Indonesian Stock Exchange (IDX) in the year 2010-2013. Based on purposive sampling method, there are 120 companies fulfilling the criterions. This research used multiple linear regression analysis. The result of this research indicates that audit committee competency and auditor specialization in industry have a negative and significant effect to tax aggressiveness. Audit tenure have a positive and significant effect to tax aggressiveness. While other variables do not have significant effect to tax aggressiveness